Analisis Tingkat Aksesibilitas Mobil Penumpang Umum Di Kabupaten Sikka - Gado, Alfridus; Gare, Mansuetus (Program Studi Teknik Sipil dan Program Studi Arsitektur Fakultas Sains & Teknologi Universitas Flores, 2022)
Sikka Regency is one of the areas located on Flores Island, East Nusa Tenggara Province. The region has many interesting natural and cultural riches, but is still hidden due to the lack of infrastructure development. These conditions affect the accessibility of public passenger cars in the Sikka Regency area. Perforated road conditions, hilly topography and narrow roads are factors that affect accessibility in the Sikka Regency area. This study aims to assess the level of accessibility of public passenger cars in the research location. The location of this research is in Paga Sub-district, Bola District and Magepanda District. The number of samples in this study was 384 people. This study uses quantitative research methods with an analysis of the level of accessibility. The results show that the level of accessibility in Paga and Bola sub-districts is moderate, which means that public passenger car access is not smooth, while the accessibility level in Magepanda sub-district is very high, which means that public passenger car access is very smooth. Recommendations from this research for local governments and local governments need to improve public passenger car facilities and improve access road connections for people in Sikka Regency.